Encountering Islam: The Politics of Religious Identities in Southeas Asia - Hui Yew Foong (ISEAS, 2013)
In Encountering Islam, the book lingers beyond the summary moment and reflects on the multiple impressions, suppressions and repressions, whether coherent or incoherent, associated with Islam as a socio-political force in public life. To this end, it is not adequate simply to represent the divergent identities associated with Islam in Southeast Asia, whether embedded in state-endorsed orthodoxy or Islamic movements that contest such orthodoxy. It is also important to examine religious minorities in political contexts where Islam is dominant and Muslim communities in national contexts where they are minorities. By situating these religious identities within their larger socio-political contexts, this volume seeks to provide a more holistic understanding of what is encountered as Islam in Southeast Asia.